Universal soft coulomb gap governs thermoelectric performance in doped conjugated polymers - Liu, Yuqian; Wei, Xiaoran; Scheunemann, Dorothea; Zhang, Maojie; Zhang, Wanlu; Kemerink, Martijn; Zuo, Guangzheng (ACS energy letters, 2025)
The power factor (PF) in doped conjugated polymers is fundamentally constrained by a trade-off between electrical conductivity and the Seebeck coefficient, yet the underlying universal limit remains unclear. Here, we identify a soft Coulomb gap near the Fermi level as the intrinsic origin of this limit, arising from long-range Coulomb repulsion among localized carriers. Combining systematic experiments and kinetic Monte Carlo simulations across chemically diverse materials, we consistently show that the maximum PF coincides with a distinct transition from Mott to Efros-Shklovskii variable-range hopping, marking the onset of gap formation accompanied by Seebeck coefficient suppression. By increasing the dielectric constant or promoting charge delocalization, the soft gap can be effectively suppressed, shifting the optimal doping range and enhancing performance. These findings establish a unifying physical framework and actionable design rules for overcoming the PF limit, with broad implications for the design of high-performance thermoelectric and other doped organic electronic materials
Gesehen am 27.02.2026